The Predictive Value of MAP2K1/2 Mutations on Efficiency of Immunotherapy in Melanoma - Ye, Ting; Zhang, Jie-Ying; Liu, Xin-Yi; Zhou, Yu-Han; Yuan, Si-Yue; Yang, Meng-Mei; Xie, Wen-Zhuan; Gao, Chan; Chen, Yao-Xu; Huang, Meng-Li; Ye, Cheng-Zhi; Chen, Jing (Frontiers in Immunology, 2022)
Background MAP2K1/2 genes are mutated in approximately 10% of melanoma patients; however, the impact of MAP2K1/2 gene alterations on the efficiency of immunotherapy has not been clarified. This study focused on the correlation between MAP2K1/2 gene mutations and the treatment response. Methods Six metastatic melanoma clinical cohorts treated with immune checkpoint inhibitors (anti-cytotoxic T lymphocyte antigen-4 (CTLA-4) or anti-programmed cell death-1 (PD-1)) were recruited in this study. RNA expression profiling results from each of these six cohorts and the Cancer Genome Atlas (TCGA) melanoma cohort were analysed to explore the mechanism related to immune activation. Results Compared to patients with wild-type MAP2K1/2, those with MAP2K1/2 mutations in an independent anti-CTLA-4-treated cohort had higher objective response rates, longer progression-free survival, and longer overall survival (OS). These findings were further validated in a pooled anti-CTLA-4-treated cohort in terms of the OS. However, there was no correlation between MAP2K1/2 mutations and OS in the anti-PD-1-treated cohort. Subgroup Cox regression analysis suggested that patients with MAP2K1/2 mutations received fewer benefits from anti-PD-1 monotherapy than from anti-CTLA-4 treatment. Furthermore, transcriptome profiling analysis revealed that melanoma tumours with MAP2K mutation was enriched in CD8+ T cells, B cells, and neutrophil cells, also expressed high levels of CD33 and IL10, implying a potential mechanism underlying the benefit of melanoma patients with MAP2K1/2 mutations from anti-CTLA-4 treatment. Conclusions MAP2K1/2 mutations were identified as an independent predictive factor for anti-CTLA-4 therapy in melanoma patients. Anti-CTLA-4 treatment might be more effective than anti-PD-1 therapy for patients with MAP2K1/2-mutated melanoma.